Efficient down-conversion ZnO codoped (Er, Yb) nanopowders synthesized via sol-gel process for Si solar cell applications. Issue 1 (March 2023) - Derouiche, Marwa; Salhi, Rached; Baklouti, Samir
Abstract: This study presents ZnO nanopowders codoped by (Er, Yb) prepared by the sol-gel process using the supercritical drying of ethanol and then annealed at 500 °C, 800 °C and 1000 °C. The molar percentage of Yb was fixed at 5%, and different molar percentages (5% and 10%) of Er at different temperatures were investigated. The structural and morphological studies show that the nanopowders are crystallized in a wurtzite ZnO structure and that the grain size is around 60 nm. The variation of the annealing temperature and the doping percentage have a significant effect on the morphology and the crystallinity of the nanopowders. Down-conversion emissions were investigated under 378 nm excitation and the (Er, Yb) codoped ZnO nanopowders exhibit interesting emissions in the green, red, and infrared ranges.